Application Suggestion of ISO 9001:2015 Quality Management System in the Defense Industry: A Literature Review - Kartono, Arif; Soediantono, Dwi (IJOSMAS, 2022)
The purpose of this article is to explore the benefits of implementing the ISO 9001:2015 quality management system in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 29 international journal articles about the application of ISO 9001:2015 from various countries and various industrial sectors. The analysis used used 29 content analysis of journal articles, then coding was carried out on the contents of the reviewed journals using the psychospiritual category. The data that had been collected was then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the implementation of the ISO 9001:2015 quality management system can increase productivity, quality, delivery, cost, morale and occupational safety and health in the industry so that the ISO 9001:2015 quality management system is recommended to be applied in the defense industry.